Sade in Italy: Deconsecrating Art. Parody Forms and Ekphrasis - David Matteini (Between, 2016)
This article analyses the parody procedures employed by the Marquis de Sade in descriptions of works of art (ekphrasis) that are found in the little-known Voyage d’Italie, account of a trip to Italy that the author made in 1775 to escape the persecution of French police. Unpublished until the nineteen sixties, nor taken into account in critical studies, this travel diary provides precious insight into many philosophical and aesthetic categories that were commonly discussed in debates in the pre-Revolutionary period. Following a substantial but fundamental section on the meagre literature about the Voyage, this essay focuses on only a few passages concerning ekphrasis in Sade’s work, enough to show how parody and satire were essential rhetorical conditions in order for the author to overturn the transcendent meaning of the works of arts as it was imposed by the Christian/Neo-platonic aesthetic tradition, which was still ruling on the intellectual milieu of the eighteenth-century grandtouristes. In accordance with the most radical tendencies of the Enlightenment - Diderot’s materialism and Shaftesbury’s philosophy of “wit” provide a good example -, in his literary debut Sade offers an ingenious and inventive framework that is well ahead of his times and, therefore, deserves further examination.